2021
DOI: 10.3390/polym13050775
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Polycaprolactone/Chitosan—Hydroxyapatite Hybrid Implants for Peripheral Nerve Regeneration

Abstract: Major efforts for the advancement of tubular-shaped implant fabrication focused recently on the development of 3D printing methods that can enable the fabrication of complete devices in a single printing process. However, the main limitation of these solutions is the use of non-biocompatible polymers. Therefore, a new technology for obtaining hybrid implants that employ polymer extrusion and electrophoretic deposition is applied. The fabricated structures are made of two layers: polycaprolactone skeleton and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The method developed in our laboratory allows extruding the PCL fiber in helix form with predefined geometry (i.e., pitch, fiber diameter) ( Figure 4 A) [ 8 ]. Moreover, the pitch can be constant or gradient ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method developed in our laboratory allows extruding the PCL fiber in helix form with predefined geometry (i.e., pitch, fiber diameter) ( Figure 4 A) [ 8 ]. Moreover, the pitch can be constant or gradient ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…This highly complex network provides control over sensation, movement, and motor coordination. Treatment of damaged peripheral nerve tissue may be pharmacologic, by transplantation (i.e., autografting, allografting, or xenografting) or by the implantation of nerve guidance conduits (NGCs) to bridge the nerve stumps, providing room and environment for nerve regeneration [ 5 , 6 , 7 , 8 ]. Conventional pharmacologic therapy is performed in the early stages of damage caused by inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The XRD patterns show the main diffraction peaks of the apatite phase with hexagonal structure (P6 3 /m, No. 176) at 2θ (hkl) equal to 25 1 shows the calculated lattice parameters (a = b and c) and cell volume (V) for both materials, indicating cell growth induced by Li + ions and, on the other hand, cell contraction after further Eu 3+ substitution. The calculated cell parameters were in good correlation with the results observed for the (0 0 2) plane shift.…”
Section: Structure Analysismentioning
confidence: 95%
“…Moreover, nHAp did not neutralize the electrophysiological activity of neurons, as Liu et al demonstrated in primary cultures of rat neurons [ 23 ]. Currently, nanotubes made in 3D printing technology from combined materials containing hydroxyapatite are also being studied [ 24 , 25 ]. In vivo studies have shown that nHAp has a beneficial effect on nerve regeneration in rats after prior spinal distension.…”
Section: Introductionmentioning
confidence: 99%